2012
DOI: 10.1158/1078-0432.ccr-12-0662
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/AKT/mTOR Pathway as a Therapeutic Target in Endometrial Cancer

Abstract: Endometrial cancer is the most common gynecologic malignancy in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
268
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(282 citation statements)
references
References 85 publications
9
268
1
4
Order By: Relevance
“…Activation of the PI3K/AKT/mTOR pathway, a signaling pathway that plays an important role in cellular growth and survival, has recently been implicated in endometrial cancer (32). Activated AKT initiates a cascade of downstream signaling events in endometrial cancer cells that promote cellular growth, metabolism, proliferation, survival, migration, apoptosis, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the PI3K/AKT/mTOR pathway, a signaling pathway that plays an important role in cellular growth and survival, has recently been implicated in endometrial cancer (32). Activated AKT initiates a cascade of downstream signaling events in endometrial cancer cells that promote cellular growth, metabolism, proliferation, survival, migration, apoptosis, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this cross-talk mechanism, regulation of tumor growth by the ER-pathway could be activated by another type of RTK signaling that is commonly seen in other types of hormonal sensitive malignancies such as breast and endometrial cancer [30,31]. Our data showed that there was no correlation between estrogen receptor and other RTK expressions (EGFR and HER2) but this was only determined by protein expression in immunohistochemistry study and was limited with regard to the number of RTKs analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream targets of mTOR include p70 ribosomal protein 6S kinase (S6K). The overactivation of the PI3K/Akt/mTOR pathway, a signaling pathway that plays a key role in cellular growth and survival, has been implicated in various tumor pathogeneses, and as such, the inhibition of the PI3K/Akt/mTOR pathway is of therapeutic interest [112][113][114]. Medici and Olsen [39] found that HemECs had constitutively active PI3K/Akt/ mTOR/p70S6K and tested their hypothesis that these cells could be sensitive to mTOR inhibitors (e.g., rapamycin).…”
Section: Hif-α-mediated Pathwaymentioning
confidence: 99%